2016
DOI: 10.18632/oncotarget.7001
|View full text |Cite
|
Sign up to set email alerts
|

MIIP accelerates epidermal growth factor receptor protein turnover and attenuates proliferation in non-small cell lung cancer

Abstract: The migration and invasion inhibitory protein (MIIP) has been discovered recently to have inhibitory functions in cell proliferation and migration. Overexpression of MIIP reduced the intracellular steady-state level of epidermal growth factor receptor (EGFR) protein in lung cancer cells with no effect on EGFR mRNA expression compared to that in the control cells. This MIIP-promoted EGFR protein degradation was reversed by proteasome and lysosome inhibitors, suggesting the involvement of both proteasomal and ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Further studies on insulin-like growth factor binding protein 2 indicated that MIIP regulates cell migration and mitosis (34). MIIP is underexpressed in a wide range of types of human cancer, including glioma, endometrial cancer, breast cancer, lung cancer, esophageal cancer, prostate cancer, neuroblastoma and pheochromocytoma (3)(4)(5)(6)(7)(8)(9)(10). A decreased MIIP expression is associated with tumorigenesis and progression of endometrial cancer as MIIP inhibits the migration and invasion of endometrial cancer cells (4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Further studies on insulin-like growth factor binding protein 2 indicated that MIIP regulates cell migration and mitosis (34). MIIP is underexpressed in a wide range of types of human cancer, including glioma, endometrial cancer, breast cancer, lung cancer, esophageal cancer, prostate cancer, neuroblastoma and pheochromocytoma (3)(4)(5)(6)(7)(8)(9)(10). A decreased MIIP expression is associated with tumorigenesis and progression of endometrial cancer as MIIP inhibits the migration and invasion of endometrial cancer cells (4).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MIIP inhibits the migration and invasion of glioma cells (6). Wen et al (5) found that MIIP accelerates epidermal growth factor receptor protein turnover and attenuates the proliferation of non-small cell lung cancer cells. Additionally, a previous study conducted by our team indicated that the expression of MIIP mRNA was reduced in human NPC cell lines (5-8F and CNE2) compared with normal nasopharyngeal epithelial cell line (NP69), and the MIIP gene played a notable role in the pathogenesis of NPC (unpublished).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Decreased acetylation activity of HDAC6 will result to α-tubulin acetylation and reduce cell migration [19]. In addition, MIIP was able to promote EGFR protein degradation and exert a negative effect on lung cancer cells' proliferation [20].…”
Section: Introductionmentioning
confidence: 99%